Umbilical cord blood concentrations of IL-6, IL-8, and MMP-8 in pregnancy complicated by preterm premature rupture of the membranes and histological chorioamnionitis - Andrys, Ctirad; Drahosova, Marcela; Hornychova, Helena; Tambor, Vojtech; Musilova, Ivana; Tosner, Jindrich; Flidrova, Eva; Kacerovsky, Marian (Neuro endocrinology letters, 2010)
OBJECTIVE: To determine whether umbilical cord blood concentrations of interleukin-6 (IL-6), interleukin-8 (IL-8), and matrix metalloproteinase-8 (MMP-8) are of value in the diagnosis of histological chorioamnionitis (HCA) and funisitis in patients with preterm premature rupture of membranes (PPROM). SETTING: Department of Obstetrics and Gynaecology, Charles University in Prague, Faculty of Medicine Hradec Kralove, University Hospital Hradec Kralove, Czech Republic. METHODS: We compared umbilical cord blood IL-6, IL-8, and MMP-8 concentrations in 83 women with PPROM between 24th and 36th gestational weeks with the presence and the absence of HCA/funisitis using nonparametric tests (Mann-Whitney U test), given the non-normal distribution of analyte. Comparisons of proportions were performed the D'Agostino and Pearson omnibus normality test and the Shapiro-Wilk test. RESULTS: Patients with HCA had a significantly higher median umbilical cord blood IL-6 concentration than patients without histological signs of inflammation (12.0 pg/mL [2.1-138.3] versus 2.7 pg/mL [0.1-12.4]; p=0.004) but did not have significantly higher median umbilical cord IL-8 (29.9 pg/mL [14.0-186.3]; versus 18.9 pg/mL [7.9-89.4]; p=0.13) and MMP-8 (2.9 pg/mL [0.5-25.2] versus 0.5 ng/mL [0.5-7.9]; p=0.18). Patients with HCA and funisitis had a significantly higher median umbilical cord blood IL-6 (222 pg/mL [95.3-411.7] versus 6.1 pg/mL [1.3-18.5]; p<0.0001) and IL-8 (20.9 pg/mL [8.4-37.7] versus 190.7 pg/mL [83.8-554.2]; p=0.0004) concentration than patients with HCA alone. Differences were not found in MMP-8 concentrations (3.7 ng/mL [0.5-21.4] versus 2.4 ng/mL [0.5-88.1]; p=0.7). CONCLUSION: HCA was associated with a significant increase in umbilical cord blood IL-6 concentration. In patients with HCA and funisitis, umbilical cord blood IL-6 and IL-8 were significantly higher than those without histological signs of inflammation.
Keywords: Fetal Membranes, Premature Rupture; interleukin-6; těhotenství; Interleukin-6; plod; mužské pohlaví; matrixová metaloproteinasa 8; Fetal Blood; Adult; interleukin-8; Infant, Newborn; ženské pohlaví; novorozenec; Humans; Pregnancy; biologické markery; předčasný odtok plodové vody; chorioamnionitida; dospělí; Fetus; Biomarkers; Chorioamnionitis; Female; Interleukin-8; Matrix Metalloproteinase 8; fetální krev; lidé; Male